Implementasi Algoritma Apriori Pada Sistem Rekomendasi Produk Rameiki Mart - Agung Bimantara Putra; Didik Indrayana; Fathia Frazna Az-Zahra (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
ABSTRACT The rapid development of technology has a very large effect in various fields. One of them is in the field of buying and selling business, which is getting higher and higher competition between business actors. One of the strategies to increase sales is to implement a recommendation for goods, but from the various categories of goods in the store, there are products that are not in demand by customers, so that if left alone, the products that are not in demand will not sell well and will make the accumulation of goods in the store, in addition to that with the many categories, it makes some customers confused to choose products that suit their wishes buyer. Therefore, the author conducts an assessment first by conducting a literature study, which finally the purpose of this study is to make it easier for users and business owners to recommend goods in the store and determine the desired product by implementing a recommendation system on the Rameiki Mart Store website which is taken from the amount of data, this is also beneficial for store owners because the existence of this recommendation system can help as a means of product promotion , as well as in recommendations for the purchase of goods. In this study, the researcher created a recommendation system using the a priori algorithm method.